World Climate. - John Bartholomew and Son (Edinburgh Geographical Institute, 1922)
Map shows early twentieth century world temperatures, thermal regions, rainfall, pressure and winds, and storm tracks and frequency. Relief shown by spot heights. Scale not indicated.